2008
DOI: 10.1016/j.cub.2008.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Sodium Current Is a Nonsynaptic Substrate for Long-Term Associative Memory

Abstract: Although synaptic plasticity is widely regarded as the primary mechanism of memory [1], forms of nonsynaptic plasticity, such as increased somal or dendritic excitability or membrane potential depolarization, also have been implicated in learning in both vertebrate and invertebrate experimental systems [2-7]. Compared to synaptic plasticity, however, there is much less information available on the mechanisms of specific types of nonsynaptic plasticity involved in well-defined examples of behavioral memory. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 22 publications
8
50
0
Order By: Relevance
“…A model of the PACAP-activated molecular cascades of memory formation after food-reward classical conditioning in Lymnaea Previous molecular, behavioral, pharmacological, and electrophysiological analyses already have identified a number of receptors, ion channels, and signaling molecules involved in the acquisition as well as early and/or late consolidation of associative LTM after food-reward classical conditioning in Lymnaea Ribeiro et al, 2003Ribeiro et al, , 2005Ribeiro et al, , 2008Fulton et al, 2005;Korneev et al, 2005;Michel et al, 2008;Nikitin et al, 2008;Wan et al, 2010). Our new findings have now made it possible to construct a model of the interacting components involved in the formation of long-term associative memory after foodreward classical conditioning in Lymnaea (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A model of the PACAP-activated molecular cascades of memory formation after food-reward classical conditioning in Lymnaea Previous molecular, behavioral, pharmacological, and electrophysiological analyses already have identified a number of receptors, ion channels, and signaling molecules involved in the acquisition as well as early and/or late consolidation of associative LTM after food-reward classical conditioning in Lymnaea Ribeiro et al, 2003Ribeiro et al, , 2005Ribeiro et al, , 2008Fulton et al, 2005;Korneev et al, 2005;Michel et al, 2008;Nikitin et al, 2008;Wan et al, 2010). Our new findings have now made it possible to construct a model of the interacting components involved in the formation of long-term associative memory after foodreward classical conditioning in Lymnaea (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in our laboratory and by others has shown that activation of NMDA receptors is necessary for the formation of associative LTM in invertebrates [Aplysia, Murphy and Glanzman (1999); Drosophila, Xia et al (2005); Lymnaea, Jami et al (2007), Wu et al (2007), and Wan et al (2010)], and we now hypothesize that invertebrate PACAP-like peptides play a mechanistic role in the learninginduced activation of NMDA receptors similar to that previously described in the hippocampus. , and K ϩ channels, Staras et al (2002) and Nikitin et al (2008); NOS and NO, Kemenes et al (2002) and Korneev et al (2005); PKA, G. ; RNA and protein synthesis, Fulton et al (2005); sGC, Ribeiro et al (2008) and Michel et al (2008)], are shown boxed. G, G-Protein; DA, dopamine; 5-HT,serotonin;MAPK,mitogen-activatedproteinkinase;CaMKII,calcium/calmodulin-dependentkinaseII;NOS,nitricoxidesynthase;NO, nitric oxide; sGC, soluble guanylyl cyclase; PKG, cGMP-activated protein kinase; PCREB, phosphorylated cAMP response element-binding protein; C/EBP, CCAAT enhancer-binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…Lymnaea stagnalis snails have been used extensively for the analysis of cellular and molecular mechanisms of locomotion (Syed and Winlow, 1991b;Pavlova, 2010;Longley and Peterman, 2013), feeding (Benjamin and Rose, 1979;Elliott and Benjamin, 1989;Kemenes and Elliott, 1994;Staras et al, 1998Staras et al, , 2003Alania et al, 2004;Vehovszky et al, 2005;Vavoulis et al, 2007;Chistopolsky and Dyakonova, 2012), respiration (Syed and Winlow, 1991a,b;Tsyganov et al, 2004;Bell et al, 2007), learning and memory (Kemenes et al, 1997(Kemenes et al, , 2002Kojima et al, 1997;Spencer et al, 1999;Staras et al, 1998;Jones et al, 2003;Sangha et al, 2003;Kemenes et al, 2006;Nikitin et al, 2008;Marra et al, 2013;Mita et al, 2014;Naskar et al, 2014), and decision making (Pirger et al, 2014;Crossley et al, 2016). There are also approaches that have been developed only in this organism, particularly the studies at the single-cell level of freshly isolated, not cultured, neurons (Dyakonova et al, 2009(Dyakonova et al, , 2015Dyakonova and Dyakonova, 2010), and experimental tests of an extracellular chemical microenvironment that has been demonstrated to play a prominent 'socializing' role in adjusting single-cell physiology to the network state (Dyakonova et al, 2015).…”
Section: Risky Decision Making By Snails In a Vital Situationmentioning
confidence: 99%
“…In the current paper, we have found a way to recover the network topology using spiking data. However, the topology is static and does not reflect the interesting dynamics of learning [6], [7]. It is certainly one of our future research topics: using sliding windows to reconstruct a dynamical network topology.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Undoubtedly, the relation between the spike activities and the synaptic couplings has been attracting increasing interests from various research fields of neuroscience [6], [7]. A basic problem is how to detect the system structure from the neural activities.…”
Section: Introductionmentioning
confidence: 99%